Experimental and theoretical analysis of rock failure characteristics by a single PDC cutter under downhole pressurized conditions - Rong, Zhun; Dai, Xianwei; Yan, Shuang; Liu, Yang; Zhang, Qi; Fu, Hao; Yao, Jianlin (Frontiers in Energy Research, 2023)
The development of high-efficiency polycrystalline diamond compact (PDC) bits plays a major role in developing unconventional oil and gas. Thereby, a series of single cutter tests have been conducted in the past few years. However, most of them were performed under atmosphere conditions due to the limitation of the experimental setup. In the present study, a series of single cutter experiments were performed under pressurized conditions, in which both principal stress and hydrostatic pressures were loaded with a self-developed facility. The cutting force, topography of cutting grooves, and mechanical specific energy (MSE) were analyzed to evaluate rock failure efficiency. Furthermore, a theoretical model was developed to study stress evolution. Combined with experimental results, the rock failure mechanism and the effects of bottom hole pressures on rock breaking characteristics were revealed. The results indicate that the increase in principal stress and hydrostatic pressures cause larger cutting forces and reduced rock cutting efficiency. Additionally, a larger hydrostatic pressure will promote the propagation of subsurface cracks, leading to larger roughness of cutting grooves and facilitating the subsequent rock cutting process. In this study, the hydrostatic pressure has the greatest impact on rock failure process, followed by the principal stress when parallel to the cutting direction. Comparing the experimental and simulation results, we can find that only a fraction of cutting force is directly utilized in breaking rocks, while the remaining force is applied to overcome the friction induced by the flow of cuttings along the cutter surface. Consequently, measures should be taken to prevent bit balling and decrease the friction force, thus weakening the effects of hydrostatic pressures and improving the efficiency of PDC bits.